2022
DOI: 10.1038/s41467-022-28414-5
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational N-degron masking by acetylation promotes proteome stability in plants

Abstract: N-terminal protein acetylation (NTA) is a prevalent protein modification essential for viability in animals and plants. The dominant executor of NTA is the ribosome tethered Nα-acetyltransferase A (NatA) complex. However, the impact of NatA on protein fate is still enigmatic. Here, we demonstrate that depletion of NatA activity leads to a 4-fold increase in global protein turnover via the ubiquitin-proteasome system in Arabidopsis. Surprisingly, a concomitant increase in translation, actioned via enhanced Targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…The extractable proteasome activity was significantly enhanced in hypk lines compared to wild type and increased to similar levels as in NatA-depleted plants ( Fig. 4F ) ( 18 ).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The extractable proteasome activity was significantly enhanced in hypk lines compared to wild type and increased to similar levels as in NatA-depleted plants ( Fig. 4F ) ( 18 ).…”
Section: Resultsmentioning
confidence: 83%
“…Of these lower abundant proteins, 81 and 94% were canonical NatA substrates (table S4; Fisher’s exact test, P < 0.0001 for the enrichment of NatA substrates in the subset of lower abundant proteins in hypk lines), strongly suggesting that lowered NTA of these NatA substrates caused their destabilization. In a companion study ( 18 ), we demonstrated that decreased NatA activity resulted in a faster turnover of NatA substrates and identified the novel nonAc-X 2 /N-degron targeting nonacetylated NatA substrates for degradation. On the basis of the findings in hypk-3 and the knowledge of the NTA-mediated stabilization of NatA substrates, we suggested that the destabilization of many other NatA substrates is compensated by enhanced translation of these proteins to maintain their steady-state level in hypk plants.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations